Prof. Dr. Luminita Silaghi-Dumitrescu at her 70th anniversary: - Editor in chief Studia UBB Chemia - The 9th of March 2021 - CRISTEA, Castelia (Studia Universitatis Babeș-Bolyai Chemia, 2021)
On the occasion of Prof. Dr. Luminita Silaghi-Dumitrescu’s 70th birthday anniversary, the editorial board of Studia Universitatis Babes-Bolyai journal, at which she is serving as Editor in Chief for Chemia series since the year 2000, wish to honor her as an outstanding member of Babes-Bolyai University’s academic community (dean of the Faculty of Chemistry and Chemical Engineering in 2000-2007, vice-rector of Babes-Bolyai University in 2008-2011) with a lifetime of academic and scientific experience characterized by great devotion, integrity and morality. It has been our privilege to be the colleagues of Prof. Dr. Luminita Silaghi-Dumitrescu and we express the best wishes to her for a good health and every success in her future endeavors.